Memory and popular festivity in Ayacucho. Communication scenarios in post-conflict societies - Rodríguez González, Yolanda (2021)
In May, the small town of Luricocha, located in the south-central Andean region of Peru, attracts numerous visitors interested in Fiesta de las Cruces (Festival of the Crosses). This festival causes the movement of dozens of communities from different neighborhoods and places of the district carrying their crosses adorned with flowers and colorful fabrics to be greeted by the parishioners and tourists. The crosses are accompanied by the Chunchos, musical and choreographic groups that play an ancestral aerophone instrument: the antara. What appears before the visitor's eyes as a ritual linked to the past is intimately intertwined with the present and its symbols of modernity: communication and information technologies. The technologies are used to activate the bonds of identity and belonging of the community and the diaspora scattered as a result of the internal war in the 80s.